Valorization of brewer's spent grain using fermentation : potential for food sustainability - Cooray, Sachindra Thilomini (2018)
Brewer’s spent grain (BSG) is a by-product generated in large quantities during beer manufacturing. Even if most of the starch content in BSG is removed during brewing, there are significant amounts of proteins, fibres and other nutrients that remain. This material is mostly disposed in landfills or given away as animal feed, without being utilized in a significant manner. Breweries are burdened due to the massive cost incurred in its disposal and the environmental implications arising therewith. Despite many studies carried out to use BSG for other valuable applications, there lies more room for further development. Furthermore, there is limited knowledge on the metabolomics variation observed when spent grain is subjected to fermentation. This study hypothesised that fermentation can be used in value addition of underutilised BSG. It is also hypothesised that an untargeted metabolomics approach can be used in monitoring the fermentation and final product. The overall aims were to (1) establish a workflow for a metabolomics study of biological processes; (2) enhance the economic value of BSG using fermentation and follow a metabolomics approach to investigate the changes taking place in this material; and (3) develop a process to extract nutrients from fermented BSG to be used in preparing a novel growth media. For the metabolomics analysis, methanol was selected to extract extracellular metabolites from samples, as it was able to extract more compounds compared to other solvents and silylation was selected as the derivatization method prior to gas chromatography separation. This developed metabolomics workflow was useful in identifying up-regulating compounds during fermentation. According to our findings, fungi fermentation improved the content of amino acids, citric acid, some vitamins and antioxidant compounds in spent grain, enhancing its nutritional value. Next the study was focused towards extracting the nutrients from the fermentation product. This extract was used in growing R. toruloides and S. cerevisiae, as a substitute for conventional growth media. The new media was able to fulfil the complete nitrogen requirement for growth, while sustaining the carotenoid and fatty acid production by R. toruloides in comparable levels to conventional growth media. According to the metabolome of the novel media, the prior fermentation step was able to increase the amino acid content of the new media. In conclusion, our hypothesis was supported and the objectives were achieved. An optimized metabolomics workflow was developed to analyse the fermentation progress. In addition, value added compounds were generated by the bioprocess to enhance the economic value of BSG. Finally, using this fermented spent grain, a novel nutrient media for yeast growth was produced. The study further demonstrates how a metabolomics investigation is important to provide information to shed light on microbial activities in biological processes, such as fermentation. Overall, fermentation can be used to add value to underutilized food waste material such as BSG. Furthermore, it facilitates the extraction of nutrients and useful bioactive compounds in lignocellulosic material. Such waste valorization methods are helpful in producing foodstuff and food ingredients as an approach to achieve food sustainability.